Calculated respiratory exposure to indoor size-fractioned polycyclic aromatic hydrocarbons in an urban environment - Kai Zhang; Zhang, Bao-Zhong; Li, Shao-Meng; Wong, Charles S.; Zeng, Eddy Y. (SCIENCE OF THE TOTAL ENVIRONMENT, 2012)
Polycyclic aromatic hydrocarbons (PAHs) associated with inhalable particles are harmful to human health, especially to people in urban indoor environments. To evaluate human respiratory exposure to indoor PAHs properly, respiratory deposition fluxes of size-fractioned PAHs were estimated based on size-segregated distribution of PAHs in indoor air of an urban community of Guangzhou, China. The concentrations of Sigma(16)PAH (sum of the 16 priority PAHs designated by the United States Environmental Protection Agency) were 28.9 +/- 10.0 ng/m(3), with the mean benzo(a)pyrene equivalent (BaPE) concentration at 4.1 +/- 1.6 ng/m(3). Particle size distributions of both Sigma(16)PAH and BaPE concentrations peaked in the 1.0-1.8 mu m fraction. The mean respiratory deposition flux of Sigma(16)PAH was 5.9 ng/h, and accumulation mode particles contributed 20.5-83.8% of the respiratory deposition fluxes for individual PAHs. In addition, 8.6-10.2% of inhaled Sigma(16)PAH were calculated to be deposited in the alveoli region, with accumulation particles as the largest contributor. In particular, ultrafine particles contributed 0.4-21.7% of individual PAHs deposited in the alveoli region, more than twice the fraction of the PAHs in the ultrafine particles (0.2-8.5%). Finally, lifetime cancer risk via inhalation of indoor particulate PAHs may be greater than the cancer risk guideline value (10(-6)). depending on specific assumptions used in this risk assessment. (C) 2012 Elsevier B.V. All rights reserved.